Technological Anxiety in the Public Sector: Exploring the Impact of Digital Factors on Personnel Performance - Kunxiang Li; Bin Wang (SocioEconomic Challenges)
The rapid development of digital technology presents challenges that necessitate an understanding of its effect on the job performance of public sector personnels to advance digital construction in the public sector. Drawing upon the Unified Theory of Acceptance and Use of Technology (UTAUT), this research delves into the pivotal influences of digital technology factors on the job performance of public sector personnels, with a specific emphasis on understanding how technology anxiety acts as a mediator in this connection. Since the purpose of this study is to explore the impact of digital technology on the work performance of public sector personnels, the research objects of this research constituency are a total of 717 public sector personnels from different public sectors. Data were collected from 717 public sector personnels using quantitative research methods and analyzed with a structural equation model in AMOS 28.0. The results show that H1,H3,H6A and H6C are not confirmed, and the other hypotheses are confirmed. Specifically, since β = -0.537 for effort expectancy, p < 0.001, and β = 0.622 for facilitating condition, p < 0.001, effort expectancy and facilitating condition have a significant promoting effect on job performance. Additionally, technology anxiety mediates the relationship between expectancy and performance. Skilled use of digital technologies is found to improve personnel performance. These findings highlight the significance of digital technology proficiency and the creation of supportive digital environments in enhancing public sector personnel performance. This study provides actionable insights for optimizing digital technologies in the public sector and improving the job performance of public sector personnels in the public sector field, highlighting the need for a training and supportive digital environment to alleviate technological anxiety and improve performance.